Reaktualisasi Pendidikan Islam Multikultural Perspektif Abdul Munir Mulkhan - Mustamar Iqbal; Moh In’ami; Afaf Afaf (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
The cultural, ethnic, and religious diversity that characterises Indonesian society can often be a source of social friction if it is not balanced with inclusive and transformative education. Islamic education, as one of the dominant education systems in Indonesia, is still often trapped in a normative-doctrinal approach that lacks multicultural awareness. This article aims to examine Abdul Munir Mulkhan's thought as a conceptual offering in the reactualization of multicultural Islamic education that is more contextual and transformative. This research uses a qualitative approach to library research by examining the primary and secondary works of Abdul Munir Mulkhan and other relevant supporting literature. The results of the study show that Mulkhan offers a model of Islamic education based on transformative humanism and substantive multiculturalism through the concept of "transcendental-praxian Islam". Islamic education, according to him, should prioritise the marginalised as its main subject, respect spiritual pluralism, and be integrated with local values. This model not only rejects religious exclusivism, but also encourages a liberating and glueing social proxy. The implications of Mulkhan's ideas encourage curriculum reformulation, teacher training, and institutional policies that are responsive to the pluralistic realities of society. This reactualization is important to prevent radicalism, strengthen social cohesion, and form an inclusive and visionary generation of Muslims. Therefore, it is recommended that Islamic education stakeholders, both from the madrasah sector, Islamic boarding schools, and universities, adopt and implement a multicultural approach based on progressive Islamic values as initiated by Abdul Munir Mulkhan